2016
DOI: 10.1080/13632469.2016.1140097
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance Assessment of Slender T-Shaped Reinforced Concrete Walls

Abstract: T-shaped slender reinforced concrete (RC) structural walls are commonly used in medium-rise and high-rise buildings as part of lateral force resisting system. Compared to its popularity, experimental results on seismic performance of these walls are relatively sparse, especially for data regarding these walls in the non-principal bending directions. This article aims at providing additional experimental evidence on seismic performance of T-shaped RC structural walls. Experimental results of six T-shaped RC wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 12 publications
4
25
0
Order By: Relevance
“…Evident increases of the peak shear strength brought by axial loads were also found in T-shaped models, regardless of the direction of lateral loading, which was also in accordance with Zhang and Li (2016) study. For models with 350 mm flange length, the average increases of the peak shear strength were approximately 17% and 12% when the axial load increased from 0.0072 to 0.0565 and 0.0565 to 0.1 f c A g , respectively.…”
Section: Parametric Study On the Peak Shear Strength Of Non-rectangulsupporting
confidence: 91%
See 2 more Smart Citations
“…Evident increases of the peak shear strength brought by axial loads were also found in T-shaped models, regardless of the direction of lateral loading, which was also in accordance with Zhang and Li (2016) study. For models with 350 mm flange length, the average increases of the peak shear strength were approximately 17% and 12% when the axial load increased from 0.0072 to 0.0565 and 0.0565 to 0.1 f c A g , respectively.…”
Section: Parametric Study On the Peak Shear Strength Of Non-rectangulsupporting
confidence: 91%
“…A reduction of the peak shear strength of 20% was also witnessed when the direction of horizontal loads changed from parallel to the web to perpendicular to the web for models with 700 mm flange length, which was far less than the difference in walls with a shorter flange. A similar decline of around 19% was also recorded in the T-shaped slender walls tested by Zhang and Li (2016), which suggested that the influence of lateral loading direction on the peak shear strength of non-rectangular walls was significant.…”
Section: Parametric Study On the Peak Shear Strength Of Non-rectangulsupporting
confidence: 70%
See 1 more Smart Citation
“…A more direct comparison of the stiffness of the wall and its impact on behaviour is given in Figure 11, which compares the pushover curves of the wall in the weak axis and the strong axis (perpendicular to the top displacement imposed in the tests). Specifically, the pushover curves in the strong axis were derived from finite-element analysis based on a similar approach to that presented by Zhang and Li (2016b), while the pushover curves for the weak axis were derived from the peak displacements from the cyclic experimental curves. Figure 11 shows the portions of the lateral stiffness of the wall in the weak axis compared with the lateral stiffness in the strong axis.…”
Section: Stiffness Of Non-rectangular Rc Walls In the Weak Axismentioning
confidence: 99%
“…Beyer et al (2008), Lowes et al (2013), Aaleti et al (2013) and Zhang and Li (2016a) conducted investigations on the seismic behaviour of non-rectangular RC walls considering different loading directions, but these studies mainly focused on walls where the length and width were similar. Previous research has indicated that the wall width could affect the stiffness (Zhang and Li, 2016a), the shear lag effect (Hassan and El-Tawil, 2003;Pantazopoulou and Moehle, 1990;Zhang and Li, 2016b) and the shear strength (Barda et al, 1977;Gulec and Whittaker, 2011;Wood, 1990) of non-rectangular RC walls. Therefore, the conclusions drawn from previous investigations on non-rectangular RC walls may need further evaluation for walls loaded in the weak axis in which the length is significantly less than the width.…”
Section: Introductionmentioning
confidence: 99%